Clear cell/endometrioid type ovarian carcinoma associated with endometriosis of the ipsilateral ovary - Rudić Biljić-Erski, Ivana; Vasiljević, Mladenko; Rakić, Snežana; Džatić-Smiljković, Olivera; Mihajlovic, Sladjana (Vojnosanitetski pregled, 2021)
Introduction. Ovarian endometriosis has been identified as a risk factor for occurrence of endometriosis-associated ovarian carcinoma. We presented a rare case of simultaneous clear cell/ endometrioid ovarian carcinoma and endometriosis of the ipsilateral ovary. Case report. A 47-year- old patient underwent surgery for right ovarian endometriotic cyst. A total hysterectomy with bilateral salpingo-oophorectomy, lymphadenectomy in the right psoas muscle region and omentectomy were performed as well as multiple peritoneal biopsies. Six cycles of chemotherapy were instituted postoperatively using the Taxol-CBDCA protocol. Abdominal and pelvic CT did not demonstrate recurrence of the disease postoperatively and after completed chemotherapy treatment. Six months after the completion of treatment, the patient felt well without the disease recurrence. Conclusion. Clear cell and endometrioid subtypes of ovarian carcinoma have good prognosis if they are diagnosed and treated at an early stage of the disease. In our patient, the carcinoma was detected in the first stage and successfully treated with combination therapy, i.e., surgical and chemotherapy.